Spectroscopic investigations of fungal biomarkers after exposure to heavy ion irradiation - Cassaro, Alessia; Pacelli, Claudia; Baqué, Mickael; Maturilli, Alessandro; Böttger, Ute; Fujimori, Akira; Moeller, R.; de Vera, Jean Pierre Paul; Onofri, Silvano (Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy, 2023)
The main objective of the ongoing and future space exploration missions is the search for traces of extant or extinct life (biomarkers) on Mars. One of the main limiting factors on the survival of Earth-like life is the presence of harmful space radiation, that could damage or modify also biomolecules, therefore understanding the effects of radiation on terrestrial biomolecules stability and detectability is of utmost importance. Which terrestrial molecules could be preserved in a Martian radiation scenario? Here, we investigated the potential endurance of fungal biomolecules, by exposing de-hydrated colonies of the Antarctic cryptoendolithic black fungus Cryomyces antarcticus mixed with Antarctic sandstone and with two Martian regolith analogues to increasing doses (0, 250 and 1000 Gy) of accelerated ions, namely iron (Fe), argon (Ar) and helium (He) ions. We analyzed the feasibility to detect fungal compounds with Raman and Infrared spectroscopies after exposure to these space-relevant radiations.